Age and breed susceptibility of dogs to trichurosis - Dolhin, O. (Scientific Progress & Innovations, 2023)
The domesticated dog (Canis lupus familiaris Linnaeus, 1758), plays an important role as a reservoir of numerous intestinal parasites that are potential sources of infection for humans, wildlife and other domestic animals. Therefore, the study of the spread of canine helminth infections in different regions of Ukraine is considered one of the important elements in ensuring epizootic well-being from parasitic diseases of both animals and humans. The aim of the study was to establish the peculiarities of age and breed susceptibility of dogs to trichurosic infection in the city of Poltava. The work was carried out in 2021‒2023 at the Laboratory of Parasitology of Poltava State Agrarian University. The research was conducted on animals of five age groups (up to 6 months, 6‒12 months, 1‒3 years, 3‒6 years, over 6 years of age) and four groups of dogs formed by breed (service, hunting, decorative, purebred, and mixed breed). Coproovoscopic studies were carried out using conventional flotation techniques. Studies have revealed a significant spread of trichurosic infection in dogs in the city of Poltava with an infection rate of 19.8 %. In the age aspect, the disease was most often detected in animals aged 6 to 12 months (EI – 31.2 %), and least of all in dogs over 6 years old (EI – 10.0 %). Among the four groups of animals formed on the basis of breed, the highest proportion of patients with trichurosis was recorded among purebred dogs and mongrels – 34.6 %, with an EI of 6.9 %, and the lowest among dogs of decorative breeds – 13.2 %, with an EI of 2.6 %. Among the hunting breeds, Labrador Retriever and Dachshund were the most infected (EI – 2.2 and 1.1 %, respectively), and Kurzhaar was the least infected (EI – 0.4 %). Among working and service dogs, the most affected by the trichurosis pathogen were Rottweiler and German Shepherd (EI – 1.0 and 0.9 %, respectively), and the least affected were Boxer, Caucasian Shepherd and Doberman Pinscher (EI – 0.2 %, 0.2 % and 0.3 %, respectively). Among decorative breeds, the most affected were pug and toy terrier (EI – 0.7 and 0.5 %, respectively). In contrast, the disease was not recorded in Pincher dogs at all. The data obtained are of both theoretical and practical value for veterinary medicine specialists, as they allow predicting the epizootic health of canine trichurosis in certain areas and developing scientifically based measures to prevent or overcome existing foci of the disease among the infected and susceptible dog population